The Influence of Effective Communication and Competency on Inpatient Knowledge of Clinical Pathway at RSUD Koja with the Monitoring System as an Intervening Variable - Alexander Romulo Hutabarat; Yanuar Ramadhan; Wahyuni Dian Purwati (Dinasti Publisher, 2025)
Quality control in healthcare services is a key factor in improving hospital service quality. This study aims to analyze the influence of effective communication and competence on quality control through a monitoring system as an intervening variable at Koja Regional Hospital. This research employs a quantitative method with a causality approach. The sample consists of 276 respondents, including inpatient doctors and nurses at Koja Regional Hospital. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results indicate that effective communication and competence have a positive and significant impact on quality control, both directly and through the monitoring system. Furthermore, the monitoring system plays a crucial role in enhancing quality control by providing accurate and real-time information on healthcare performance. The implications of this study highlight the importance of improving communication skills and healthcare worker competence, as well as optimizing the monitoring system to ensure better quality control implementation in hospitals